Optimal Split Ratio in Double-Stator Permanent-Magnet Motors Considering Loss Limitations for Robot Joint Applications - Tianran He; Yang Shen; Wei Li; Dawei Liang (Energies)
Recently, humanoid robots with personification behavior and high working efficiency have received significant attention. Meanwhile, high-torque-density motors, which serve as the core power source for robot joints, have also been widely researched. In this paper, a high-torque-density double-stator permanent-magnet (DSPM) motor is designed for robot joint applications, and its outer stator (OS) split ratio (the ratio between the inner and outer diameters of the OS) and inner stator (IS) split ratio (the ratio between the inner and outer diameters of the IS) are analyzed and optimized. Since the DSPM motor has different heat dissipation capabilities for the OS and IS, their different loss limitations should be considered to avoid the risk of local overheating, especially for the IS. This paper shows that the loss limitations affect the optimal OS and IS split ratios, as well as the maximum average torque. The IS loss limitation increases the optimal OS split ratio and decreases the optimal IS split ratio; however, the OS loss limitation has the opposite effect. Additionally, an investigation into the electromagnetic characteristics of the optimized DSPM motor was conducted using the finite element method. Finally, a prototype was manufactured, and the results of the temperature rise experiments verified the feasibility of the proposed DSPM motor and the effectiveness of the optimal method.